The synergistic impact of climate change and COVID-19 on gut health in Africa - Elwakil, Reda; Elsahhar, Medhat; Fouad, Yasser; Ocama, Ponsiano; Ng’wanassai, Masolwa (Medical & Clinical Research, 2021)
Agriculture represents the cornerstone of Africa’s economy and accounts for the majority of livelihoods across the continent. Therefore, African countries economy is highly exposed for climate change impacts. Countries with low-middle income are highly affected by extreme weather and climate events and are often overrepresented in the number of individuals displaced by these events. On the other hand, the poorest continent, Africa with the most vulnerable populations to infectious diseases, is predicted to be significantly affected by the ongoing COVID-19 outbreak. Currently there are no studies in the literature addressing the synergistic impact of climate change and COVID-19 on gut health in Africa. The African Middle East Association of Gastroenterology (AMAGE) and the Clinical Research Committee of the World Gastroenterology Organization (WGO) had established a joint research group called Climate change in Africa Group (CCAG) to study this point. Aim of the Work: The aim of the current review is to study the synergetic impact of both climate change and COVID-19 pandemic on gut health in Africa. Conclusion: Climate change events lead to planned and unplanned migrations with emerging new zoonotic disease due to increased exposure of humans to animals. Drastic overwhelming global events carry the risk of water scarcity, food insecurity and population gathering in camps which may increase the prevalence of water-born , food-born and vector-borne diseases. The low-middle income countries are highly affected by extreme weather and climate events and are often over represented in the number of individuals displaced by these events. Africa with the most vulnerable populations to infectious diseases is predicted to be significantly affected by the ongoing COVID-19 pandemic.
Keywords: Africa; Climate change; COVID-19; SARS COV2